2016
DOI: 10.1016/j.ijdevneu.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

How various drugs affect anxiety‐related behavior in male and female rats prenatally exposed to methamphetamine

Abstract: Different forms of anxiety-related behavior have been reported after a single drug use of many abused substances, however, less is known about how males and females are affected differently from exposure to various drugs. Furthermore, chronic prenatal methamphetamine (MA) exposure was shown to predispose the animal to an increased sensitivity to drugs administrated in adulthood. Using the Elevated plus-maze test (EPM), the first aim of the present study was to examine how male and female rats are affected by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 81 publications
(109 reference statements)
3
7
1
1
Order By: Relevance
“…Our studies demonstrated that increased susceptibility to MA and amphetamine (Macúchová et al 2016(Macúchová et al , Šlamberová et al 2011 after prenatal administration of MA using the Laboras test and the open arena test, both of which showed increased locomotor and exploratory activity after exposure. In females, crosssensitization was also found after acute administration of MDMA and cocaine (Šlamberová et al 2013), suggesting sex differences relative to acute drug administration.…”
Section: Hypothesis II -Prenatal Ma Exposure Changes Drug Susceptibilsupporting
confidence: 51%
“…Our studies demonstrated that increased susceptibility to MA and amphetamine (Macúchová et al 2016(Macúchová et al , Šlamberová et al 2011 after prenatal administration of MA using the Laboras test and the open arena test, both of which showed increased locomotor and exploratory activity after exposure. In females, crosssensitization was also found after acute administration of MDMA and cocaine (Šlamberová et al 2013), suggesting sex differences relative to acute drug administration.…”
Section: Hypothesis II -Prenatal Ma Exposure Changes Drug Susceptibilsupporting
confidence: 51%
“…Furthermore, animal studies typically involve un-signaled, non-contingent cannabinoid administration by the experimenter, which is presumably stressful compared to self-administration, the mode of cannabinoid intake by humans seeking to reduce anxiety/ stress. We found only one published study that included a comparison of cannabinoid effects on anxiety-like behavior in adult (PND60 or older) male vs female rats: on the elevated plus-maze, a moderate dose of THC (2 mg/kg) increased closed arm time and decreased stretch-attend postures (peering out to open arms from closed arms) in female but not male rats, suggesting increased anxiety-like behavior in females only (Macúchová et al, 2016). Several studies have examined acute cannabinoid effects on anxietylike behavior in adolescent female vs male rats, with variable results: for example, the synthetic cannabinoid CP55,940 was more potent in PND44 females than males in increasing anxiety-like behavior on the elevated plus-maze (Marco et al, 2006), whereas 2 mg/kg THC was anxiolytic in both sexes tested on PND35 (Harte-Hargrove and Dow-Edwards, 2012).…”
Section: Potential Therapeutic Effects Of Cannabis and Cannabinoidsmentioning
confidence: 99%
“…Preclinical studies have shown analogous results, i.e. poor pregnancy results such as development of neonatal reflexes (McDonnell‐Dowling and Kelly, 2015a) after oral or subcutaneous administration (McDonnell‐Dowling and Kelly, 2016), memory impairment (Fialova et al, 2015; Macuchova et al, 2014; Slamberova et al, 2014) and increased anxiety in the adult offspring as assessed by different behavioural tests (Macuchova et al, 2016; Slamberova et al, 2015). In a similarly designed study a challenge dose of methamphetamine in adulthood in animals prenatally exposed to the same drug led to higher epileptiform neuronal activity in female rats (Matejovska et al, 2014).…”
Section: Introductionmentioning
confidence: 90%